The Oxford handbook of structural transformation - Monga, Célestin; Lin, Justin Yifu, 1952- (Oxford : Oxford University Press, 2019)
'The Oxford Handbook of Structural Transformation' addresses the economics of structural transformation around the world. It deals with major themes, which include history and context, critical issues and concepts, methodological foundations, main theoretical approaches, policy issues, some illuminating country experiences of structural transformation, and important debates on the respective roles of the market and the state in that process. The historical record provides a challenge for economists to understand the success of the rising economic powers (some of them initially considered unlikely candidates for prosperity) and the stagnation or decline of others.
Structural Transformation, Deep Downturns, and Government Policy / Joseph E. Stiglitz -- Location Fundamentals, Agglomeration Economies, and the Geography of Multinational Firms / Laura Alfaro, Maggie Xiaoyang Chen -- Sustainable Structural Change in the Context of Global Value Chains / Pauline Lectard -- Participation in Global Value Chains: Challenges and Opportunities / Xubei Luo, Gary Gereffi -- Building Effective Clusters and Industrial Parks / Xiaobo Zhang -- Infrastructure Finance: Mobilizing Long-Term Liability Embedded Funds from International Institutional Investors to Emerging Markets / Kevin Lu, Cledan Mandri-Perrott -- Measuring Structural Change / Célestin Monga, Samuel Standaert -- Transforming Traditional Agriculture Redux / Philip G. Pardey, Julian M. Alston -- Manufacturing and Employment in Large Countries / Nobuya Haraguchi -- Global Megatrends and the Macroeconomics of Gender / Kalpana Kochhar, Sonali Jain-Chandra, Monique Newiak -- The Transformation of Latin American Economies / José Antonio Ocampo -- Structural Transformation and Growth: Theoretical Considerations / Richard Rogerson -- India's Path to Transformation: An Exception to the Rule / Deepak Nayyar -- Structural Transformation in Egypt, 1965-2015 / Khalid Ikram -- Growth and Structural Transformation in Viet Nam: The Real Story Beneath / Dang Thi Thu Hoai, Finn Tarp, Dirk van Seventer -- Economic Reform and Structural Change: The Chinese Experience / Barry Naughton -- Financing Industrial Development in Korea and Implications for Africa / Keun Lee -- How Taiwan Managed to Grow: Structural Transformation and Industrial Policy / Wan-wen Chu -- Ethiopia: Lessons from an Experiment / Arkebe Oqubay -- Economic Transformation in Africa from the Bottom Up: New Evidence from Tanzania / Xinshen Diao, Josaphat Kweka, Margaret McMillan -- Growth and Structural Transformation in the WAEMU Countries / Tchétch
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on March 11, 2019).
Keywords: Economic development